WHEN COURTS DO POLITICS : public interest law and litigation in east africa. - OLOKA-ONYANGO, J. (Cornell Institure for African Development series, 2017)
Using the phenomenon of public interest litigation (PIL) as the primary focus of analysis, this book explores the manner in which the judicial branch of government in the three East African states of Kenya, Tanzania and Uganda has engaged with questions traditionally off-limits to adjudication and court-based resolution. It is rooted in an incisive investigation of the history of politics and governance in the sub-region, accompanied by an extensive repertoire of judicial decisions. It also provides a critical and informative account of the manner in which courts of law have engaged with State.